2016
DOI: 10.12973/eurasia.2017.00625a
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Technologies to Develop Visual-Spatial Ability in Engineering Students

Abstract: The present study assessed a short training experiment to improve spatial abilities using two tools based on virtual technologies: one focused on manipulation of specific geometric virtual pieces, and the other consisting of virtual orienteering game. The two tools can help improve spatial abilities required for many engineering problem-solving procedures. The results indicated that training activities improved the components of space ability (mental rotation, spatial visualization, and spatial orientation). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 50 publications
4
37
0
4
Order By: Relevance
“…Most recent research (Roca-González et al, 2017) on the development of the spatial orientation skill, in which the use of maps was combined with VR, showed similar gains as those obtained with the SDI, GISc and AR workshops. This, together with the results obtained in the present research, confirms the importance of cartography as a complement to virtual reality and another methodologies and techniques for the acquisition of spatial ability.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 65%
See 1 more Smart Citation
“…Most recent research (Roca-González et al, 2017) on the development of the spatial orientation skill, in which the use of maps was combined with VR, showed similar gains as those obtained with the SDI, GISc and AR workshops. This, together with the results obtained in the present research, confirms the importance of cartography as a complement to virtual reality and another methodologies and techniques for the acquisition of spatial ability.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 65%
“…Some references have been cited in which the result by gender is similar (Roca-González et al, 2017;Carbonell et al, 2011;Carbonell et al, 2012;Carbonell and Bermejo 2017), although there is also other research that concluded otherwise (Carbonell, 2017). Liu et al (2011) found, in study of gender with different orientation strategies, that there was no difference in tasks related to spatial orientation like landmark recognition and left-right orientation, and that males were better than females in path reversal and cognitive maps.…”
Section: Discussion Conclusion and Future Workmentioning
confidence: 82%
“…While most literature focused on the techniques and tools for improving the abilities of spatial relations, spatial visualization, or spatial orientation (Alqahtani et al, 2017;Nagy-Kondor, 2017;Roca-González et al, 2017), the present study focused on training the synthesis ability of proportion estimation. Furthermore, the experimental S3D system provided users with binocular depth cue, overcoming the limitation of traditional Virtual Reality or Augmented Reality systems that offered only monocular depth cues.…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the spatial ability (i.e., spatial relations, spatial visualization, and spatial orientation) of new engineering students, VR and AR were used in a training experiment (Roca-González, Martin-Gutierrez, García-Dominguez, & Carrodeguas, 2017). Recently, stereoscopic 3D (S3D) displays, which have binocular disparity, have been used to present teaching materials for product design education or architecture design education (Smith et al, 2005;Chen, Cheng, Chu, & Sandnes, 2015).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…Τα VLE έχουν δείξει μεγάλες δυνατότητες στη διδασκαλία και τη μάθηση και συμβάλουν ουσιαστικά τόσο στη συνεργατική μάθηση όσο και στη μάθηση βασισμένη σε προβλήματα (Duncan et al, 2012). Ψηφιακά εργαλεία βασισμένα σε εικονικές τεχνολογίες βοηθούν ιδιαίτερα στη βελτίωση των χωρικών δυνατοτήτων, ειδικότερα παιχνίδια βασισμένα σε εικονική περιστροφή βελτιώνουν σημαντικά τις χωρικές ικανότητας που απαιτούνται σε πολλές διαδικασίες μηχανικής επίλυσης προβλημάτων (Roca-González et al, 2017). Η εξοικείωση με σχηματικές αναπαραστάσεις σχετίζεται και αναπτύσσει τις δεξιότητες επίλυσης προβλήματος (vanGarderen & Montague, 2003).…”
Section: εισαγωγήunclassified